THE EFFECT OF PROVIDING EDUCATIONAL VIDEOS TOWARDS KNOWLEDGE, ATTITUDE, AND BEHAVIOURS RELATED TO REPRODUCTIVE HEALTH, STIs, AND HIV/AIDS IN NON-MEDICAL COMMUNITIES - Nik Ahmad Rashdan; Theakirana Firdaus; Asy Syifa Karima; Nur Nadia; Holipah Holipah (Journal of Community Health and Preventive Medicine, 2021)
Reproductive Health is important to prevent Sexually Transmitted Diseases (STDs). The previous study showed that the young people have a low knowledge, and low attitude and behavior regarding reproductive health especially for non-medical community. Video education is known as one of the effective health promotion media. This research aims to know the factor that influences knowledge and attitude towards reproductive health and improving their knowledge, attitude and behavior about reproductive health. This study used a pre-experimental method with a one-group pretest-posttest design. The population in this study infinite population. The population in the reproductive age around 20-30 who did not work in the medical field randomly chosen online. The data were analyzed by descriptive analysis and analytical statistics (Wilcoxon test). The knowledge of respondents towards the health of reproduction and diseases related has increased in the value of the average of pre-intervention as much as 64.48 to 84.43. Respondents' attitudes also improved from the value of 79.51 to 89.55 after watching the educational video. Educational video can increase knowledge related to the health of reproduction, STDs, and HIV/AIDS, and improve the attitude of the respondents to the diseases and screening before marriage.